Multiple components of the nuclear pore complex interact with the amino-terminus of MX2 to facilitate HIV-1 restriction - Dicks, Matthew DJ; Betancor, Gilberto; Jimenez-Guardeño, Jose Manuel; Pessel-Vivares, Lucie; Apolonia, Luis; Goujon, Caroline; Malim, Michael H. (Public Library of Science, 2018)
Human myxovirus resistance 2 (MX2/MXB) is an interferon-induced post-entry inhibitor of human immunodeficiency virus type-1 (HIV-1) infection. While the precise mechanism of viral inhibition remains unclear, MX2 is localized to the nuclear envelope, and blocks the nuclear import of viral cDNAs. The amino-terminus of MX2 (N-MX2) is essential for anti-viral function, and mutation of a triple arginine motif at residues 11 to 13 abrogates anti-HIV-1 activity. In this study, we sought to investigate the role of N-MX2 in anti-viral activity by identifying functionally relevant host-encoded interaction partners through yeast-two-hybrid screening. Remarkably, five out of seven primary candidate interactors were nucleoporins or nucleoporin-like proteins, though none of these candidates were identified when screening with a mutant RRR11-13A N-MX2 fragment. Interactions were confirmed by co-immunoprecipitation, and RNA silencing experiments in cell lines and primary CD4+ T cells demonstrated that multiple components of the nuclear pore complex and nuclear import machinery can impact MX2 anti-viral activity. In particular, the phenylalanine-glycine (FG) repeat containing cytoplasmic filament nucleoporin NUP214, and transport receptor transportin-1 (TNPO1) were consistently required for full MX2, and interferon-mediated, anti-viral function. Both proteins were shown to interact with the triple arginine motif, and confocal fluorescence microscopy revealed that their simultaneous depletion resulted in diminished MX2 accumulation at the nuclear envelope. We therefore propose a model whereby multiple components of the nuclear import machinery and nuclear pore complex help position MX2 at the nuclear envelope to promote MX2-mediated restriction of HIV-1.
Keywords: Agentes antivíricos; Virus; Virology; VIH